vp100813_elic_VerbalForms_Imperative_Negative_Positive_S_SOsg_1 - Валентина Пуяковна Силкина (Надер); Олеся Ханина (Bernard Comrie, 2010)
О.Ханина собирает с В.П.Надер императив - отрицательный всех лиц и чисел и положительный только 3го лица: 1я часть - субъектное и начало субъектно-объектного спряжения с ед.числом объекта O.Khanina collects with V.P.Nader Imperative - negative for all persons and numbers, positive for 3rd person only: 1st part - subject and the beginning of subject-object with singular object Language_Name: Enets Language_Region: Asia Language_Country: Russia Project_Status: Complete Year: 2007 Start_Date: 2008-02-01 End_Date: 2011-01-31 Title vp100813_elic_VerbalForms_Imperative_Negative_Positive_S_SOsg_1